Tent Space Approach of Morrey Spaces and Their Application to Duality and Complex Interpolation. (16th January 2023) - Ono, Takahiro
Abstract : The aim in this paper is to establish a new duality property of Morrey spaces and to discover the complex interpolation space between Morrey spaces and Lebesgue spaces. For that purpose, a new space N p, q s R n is introduced by using methods of tent spaces. The space generalizes Morrey spaces and Lebesgue spaces. Furthermore, this scale of spaces is amenable to the complex interpolation space.